The Interpretation of Ahlul Bait on Tafsir al-Misbah: The Julia Kristeva Intertextuality Perspectives - Hayati, Safira Malia; Sofia, Adib; Zikri, Arfad; Siddiq, Taufiqul (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This article aims to analyze the interpretation of Ahlul Bait in Al-Mishbah (a Tafsir created Shihab ) by Kristeva’s intertextuality theory. This study used thematic method, which examined in accordance with the the theme. Tafsir Al-Mishbah serves as the primary source for this research, beside using library research, with publications about the subject serving as secondary sources. The interpretation of Ahlul Bait is inextricably linked to his impact over other interpretations, such as Al-Mizan's. Shia's impression of him are suggested tobe examined because in his perspective, there is no attitude in an objective problem; rather, people will adopt and affected by their surroundings, upbringing, and educational and social experiences.